The Contribution of Lecturer Pedagogical Competence, Intellectual Intelligence and Self-Efficacy of Student Learning Motivation - Panni Ance Lumbantobing (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to investigate the contribution lecturers’ pedagogical competences, intellectual intelligence and self-efficacy of student learning motivation. The analysis technique in this study is a multiple regression and comparison technique. It observes the relationship or influence among three variables. The sample of this study consisted of 30 students. The validity test results for each variable of lecturer pedagogical competence, intellectual intelligence, self-efficacy, and student learning motivation are valid, while the reliability of each variable is all reliable. The research findings show that the results of the analysis obtained the price of Fhit = 371,862, db = (3.26), p-value = 0,000 <0.05, Ho is rejected. The price of R2 = 0.977, Fhit = 371,862, db = (3.26) p-value = 0,000 <0.05 or Ho is rejected. The contribution of lecturers 'pedagogical competence, intellectual intelligence and self-efficacy to students' learning motivation is 0.977 or 97.7%. Thus, lecturers' pedagogical competence, intellectual intelligence and self-efficacy simultaneously influence student learning motivation.